O14 Semi-quantitative assessment of synovial inflammation on US guided synovial membrane biopsy is contingent to disease phase, autoimmune profile and treatment response in RA: a large single center experience. (20th April 2020) - Alivernini, Stefano; Tolusso, Barbara; Gessi, Marco; Gigante, Maria Rita; Petricca, Luca; Mario, Clara Di; Perniola, Simone; Fedele, Anna Laura; Peluso, Giusy; Bui, Laura; Capacci, Annunziata; Federico, Francesco; et al.
Abstract: Background: Ultrasound (US)-guided minimally-invasive synovial tissue (ST) biopsy is a well-tolerated procedure for basic and translational studies on chronic inflammatory joint diseases as rheumatoid arthritis (RA), psoriatic arthritis (PsA) and spondyloarthritis (SpA). The aim of the study was to evaluate the utility of histopathologic criteria to differentiate US-guided ST biopsies in daily clinical care in relation to diagnosis, disease characteristics, US parameters and treatment response in a large single center ST biopsy unit. Methods: 1, 064 patients [545 RA, 167 PsA, 75 SpA, 199 undifferentiated peripheral inflammatory arthritis (UPIA), 18 crystal arthritis, 26 connective tissue diseases and 34 osteoarthritis (OA) respectively] who underwent US-guided ST biopsy were enrolled. US parameters (Synovial Hyperthrophy and Power Doppler signal respectively) were recorded for each biopsied joint. RA, PsA and SpA patients were stratified based on disease activity phase (naive to DMARDs, DMARDs resistant and in sustained remission, respectively). Clinical, demographic and immunological characteristics were recorded for each patient. All ST FFPE specimens were routinely processed and stained with H&E and classified by a pathologist, blinded to clinical characteristics, using the Krenn score to assess the degree of ST inflammation. Moreover, the presence/absence of lymphocytes, plasmacells, granulocytes and oedema was assessed for each ST. All naive to treatment RA were treated according to the T2T scheme and followed for at least 12 months and DAS remission rate was recorded. Results: In the cohort, the distribution of synovitis score was significantly different among patients with inflammatory chronic diseases (RA, PsA, SpA and UPIA respectively) compared to OA (ANOVA Test p < 0.001). Moreover, Krenn score directly correlated with synovial hyperthrophy (R = 0.36; p < 0.001) and Power Doppler signal (R = 0.40;p<0.001) of the biopsied joint. Considering the RA cohort, naive RA showed a higher Krenn score compared to resistant RA (p < 0.001) and RA in sustained clinical and US remission (p < 0.001), directly correlating with DAS28 (R = 0.51; p < 0.001). Moreover, ACPA and RF positivity was related to the Krenn score and to ST plasmacells presence at RA onset (p < 0.05 and p < 0.001, respectively) but not at the time of DMARDs-failure or sustained remission achievement (p > 0.05 for both). Stratifying naive RA based on disease duration at ST biopsy, naive RA with symptoms duration >1 year, showed higher Krenn score compared to those with symptoms duration <3 months (p < 0.001). Finally, logistic regression analysis revealed that Krenn score higher or equal to 4.5 at baseline is an independent factor of no DAS remission achievement within 12 months [OR(95%CI):0.37(0.20-0.67)p<0.001] in naive RA. Conclusion: Krenn score is a reliable tool for the semi-quantitative assessment of ST inflammation on US-guided ST biopsies being differentially distributed among various chronic inflammatory joint diseases and contingent to disease phase, autoimmune profile and therapeutic response in RA. Disclosures: S. Alivernini None. B. Tolusso None. M. Gessi None. M. Gigante None. L. Petricca None. C. Di Mario None. S. Perniola None. A. Fedele None. G. Peluso None. L. Bui None. A. Capacci None. F. Federico None. G. Ferraccioli None. E. Gremese None.